Energy saving electrochromic windows from bistable low-HOMO level conjugated polymers. Issue 1 (9th December 2015) - Shin, Haijin; Seo, Seogjae; Park, Chihyun; Na, Jongbeom; Han, Minsu; Kim, Eunkyoung
Abstract : Energy saving electrochromic windows were achieved by controlling the interfacial charge transfer using low-HOMO level ( E HOMO < −5 eV) π-conjugated polymers (CPs) as bistable electrochromic films and an ionic liquid as the electrolyte layer. It provided a long bistability (>90 min) at the voltage-off state with a high coloration efficiency (879 cm 2 C −1 ). Abstract : Energy saving electrochromic windows were established by controlling the interfacial charge transport using low-HOMO level (<−5 eV) π-conjugated polymers as bistable electrochromic films and an ionic liquid as the electrolyte. It provided a long bistability (>90 min) at the voltage-off state with a high color contrast (879 cm 2 C −1 ).